The effect of storytelling intensity on the empathy abilities: a study in madurese elementary school age children - Yudho Bawono; Wasis Purwo Wibowo; Puji Restu Aditiya; Ar Liza Listiyana; Samsul Muarif (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
In recent years, news about the degenerate in empathy has been increasingly found, even this degenerate in empathy also occurs in children. While the ability to empathize itself can actually be taught since childhood. The technique to develop empathy ability in childhood is through the intensity of storytelling. This study aims to determine the role of storytelling intensity in developing the empathy ability of elementary school age children. Quantitative research was conducted with 233 participants from SDN Kraton 1 and SDN Kraton 2 Bangkalan Regency, Madura aged 10-11 years (grades IV and V). Data analysis using Simple Linear Regression. The results of the study indicated that storytelling intensity can develop the empathy ability of elementary school age children. The results encouraged parents at home and teachers at school to provide fairy tales intensively to children. At home, storytelling can be done more flexibly, while at school, storytelling can be given by adjusting the curriculum for grades IV and V of elementary school.